POLITYK JAKO ZWYKŁY NIEZWYKŁY CZŁOWIEK W MEDIACH. ANALIZA WIZERUNKÓW POLITYCZNYCH W KONTEKŚCIE ZWYKŁOŚCI - Przybysz, Łukasz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The paper focuses on the analysis of strategies to create the image of politicians being presented in the media as ordinary people. The paper presents and analyses the profiles of Polish and foreign politicians. An attempt has been made to look at the effectiveness of the offered solutions and to present a critical analysis of the actions taken. There has also been an effort taken to identify which strategies and tactics politicians use to exist in public consciousness. Furthermore, the paper raises the issue of the roles which politicians are put in. The concept of mediatisation of politics and social life is the axis of the presented considerations.